ANALYSIS OF INVESTMENT PROJECTS IN THE CONDITIONS OF UNCERTAINTIES - Kussainov Ч.К.; Shukayev Д.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
This article discusses methods from the theory of games with nature for the analysis of scenarios of investment projects in conditions of uncertainty based on the ranking method. Among the methods of game theory, the criterion of Maximax, Hurwitz, Laplace, Wald, Savage and Bayes is used. It is worth highlighting the use of the universal gamma distribution of random variables when using the Hurwitz criterion. The Borda voting method is used as a ranking method. The following financial indicators are considered as input data for the algorithm: net present value, internal rate of return, profitability index, payback period and return on investment. As a result, a hybrid algorithm for choosing an effective investment project is proposed based on scenario analysis, ranking method and game theory methods. As a demonstration of the results of the hybrid algorithm, a test set of empirical data was used.